IMMEDIATE AND MIDTERM RESULTS OF BALLOON AORTIC VALVULOPLASTY IN CHILDREN WITH AORTIC VALVE STENOSIS WITH SPECIAL REFERENCE TO DYSPLASTIC AORTIC VALVE - Wazir, Haseen Dil; Qureshi, Ahmad Usaid; Hyder, Syed Najam; Sadiq, Masood (Journal of Ayub Medical College Abbottabad, 2019)
Background: This study was conducted to determine the immediate and midterm outcome of balloon aortic valvuloplasty in children from age 1 month to 16 years, with special reference to mean balloon to aortic valve ratio along with dooming versus dysplastic valve. Methods: This was a retrospective cohort study. Patients who underwent balloon aortic valvuloplasty in a single tertiary care hospital were reviewed regarding immediate outcome, morphology of aortic valve, mean balloon to aortic valve ratio and complications during procedure from January 2006 till December 2016. Results: Of 171 patients, 80.11% had fall to good results while 73.1% had adequate outcome. Mean gradient fall of more than 50% or Peak systolic gradient decreased significantly post ballooning, which indicates good results. The age ranges from 1-92 months, 89.4% patients from age group less than1 year had adequate outcome, (p=0.017). In terms of morphology, 55.6% cases had doming while 44.4% cases had dysplastic aortic valve. There was no significant difference between dysplastic and doming valves in terms of outcome (p=0.224). Only 6 patients (3.5%) developed significant aortic regurgitation. Regarding short-term and intermediate outcome 92% of the patient were free from a second intervention and there was no significant difference between complications regarding balloon to aortic valve ratio also. Conclusion: Our 10-year experience showed that balloon aortic valvuloplasty is a safe and effective therapy, irrespective of age groups. The complications rate is low and good outcome is achieved by keeping balloon to aortic valve ratio of ±0.9 irrespective of morphology of valve. Keywords: Children; Congenital aortic valve stenosis; Balloon aortic valvuloplasty